Molecular identity of Nemoura lacustris (Plecoptera: Nemouridae) throughout its distributional range - Fochetti, Romolo; Oliverio, Marco; Russini, Valeria; Tapia, Gloria; de Figueroa, Josè Manuel Tierno (Zootaxa, 2019)
The recent report of Nemoura lacustris Pictet, 1865 in Great Britain has raised doubts on its identity, given the isolation with respect to the Mediterranean and continental populations of this species. Using molecular analyses, we tested if populations from  the United Kingdom and the Iberian Peninsula were conspecific and tested the hypotheses of a recent colonization event versus a more ancient origin for the British populations. Phylogenetic analysis of the mitochondrial marker COI allowed us to conclude that the United Kingdom specimens morphologically ascribed to N. lacustris were conspecific with populations from France and the Iberian Peninsula. Based on the genetic divergence of the two reciprocally monophyletic clades from the Iberian Peninsula and Great Britain/France, respectively, the present distribution of N. lacustris can be postulated as a relatively recent dispersal or introduction into Great Britain from France.                Finally, we note the isolated position displayed by N. lacustris in the phylogenetic tree of Nemoura species based on COI sequences, as the sister to all included species of the genus. This isolated position corresponds with the specific morphology of N. lacustris genitalia and requires additional studies to ascertain clearer generic boundaries within the Nemouridae.-